Data: Gene expression profile in peripheral B-lymphocytes and sera of individuals with fibromyalgia - Klar, Joakim (Uppsala University, 2022)
Overview

Fibromyalgia (FM) is an idiopathic chronic disease characterized by widespread musculoskeletal pain, hyperalgesia and allodynia, often accompanied by fatigue, cognitive dysfunction and other symptoms. We investigated the gene expression profile in peripheral B-cells in FM patients and healthy matched control individuals.

Summary

The uploaded data consist of count table and sample information and can be used for gene expression analysis of patients and controls.

Generation of Data

A total of 100 ng of RNA from purified B-cells of each participant (26 patients and 23 controls) was used for sequencing following rRNA depletion and library preparation (TruSeq stranded mRNA library preparation kit, cat# 20020595, Illumina Inc.). Unique dual indexes (cat# 20022371, Illumina Inc.) were used according to the manufacturers’ protocol (#1000000040498). The quality of libraries was evaluated using the Fragment Analyzer from Advanced Analytical (AATI) using the DNF-910 kit and adapter-ligated fragments were quantified by qPCR using the Library quantification kit for Illumina (KAPA Biosystems) on a CFX384Touch (Bio-Rad) prior to cluster generation and sequencing. Sequencing was carried out on an Illumina NovaSeq 6000 instrument (NovaSeq control software v 1.7.0/ RTA v3.4.4) according to the manufacturers’ instructions. Demultiplexing and conversion to FASTQ format was performed using the bcl2fastq2 (v2.20.0.422) software, provided by Illumina.

Data

Count Data: Samples were analyzed with the nf-core RNA sequencing pipeline release 1.4.2 (github.com/nf-core/rnaseq). In brief, the pipeline processes raw data from FastQ inputs, aligns the reads, generates counts relative to genes or transcripts.

Sample Data: Information regarding SampleName, Sample and Condition
Keywords: Gene expression (incl. microarray and other genome-wide approaches); Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik